PPARG: A Promising Therapeutic Target in Breast Cancer and Regulation by Natural Drugs - De-Hui Li; Xu-Kuo Liu; Xiao-Tong Tian; Fei Liu; Xu-Jiong Yao; Jing-Fei Dong (PPAR Research)
Breast cancer (BC) is the most common type of cancer among females. Peroxisome proliferator-activated receptor gamma (PPARG) can regulate the production of adipocyte-related genes and has anti-inflammatory and anti-tumor effects. Our aim was to investigate PPARG expression, its possible prognostic value, and its effect on immune cell infiltration in BC, and explore the regulatory effects of natural drugs on PPARG to find new ways to treat BC. Using different bioinformatics tools, we extracted and comprehensively analyzed the data from the Cancer Genome Atlas, Genotype-Tissue Expression, and BenCaoZuJian databases to study the potential anti-BC mechanism of PPARG and potential natural drugs targeting it. First, we found that PPARG was downregulated in BC and its expression level correlates with pathological tumor stage (pT-stage) and pathological tumor-node-metastasis stage (pTNM-stage) in BC. PPARG expression was higher in estrogen receptor-positive (ER+) BC than in estrogen receptor-negative (ER−) BC, which tends to indicate a better prognosis. Meanwhile, PPARG exhibited a significant positive correlation with the infiltration of immune cells and correlated with better cumulative survival in BC patients. In addition, PPARG levels were shown to be positively associated with the expression of immune-related genes and immune checkpoints, and ER+ patients had better responses to immune checkpoint blocking. Correlation pathway research revealed that PPARG is strongly associated with pathways, such as angiogenesis, apoptosis, fatty acid biosynthesis, and degradation in ER+ BC. We also found that quercetin is the most promising natural anti-BC drug among natural medicines that upregulate PPARG. Our research showed that PPARG may reduce BC development by regulating the immune microenvironment. Quercetin as PPARG ligands/agonists is a potential natural drug for BC treatment.